Application of Multiple Intelligence Theory in the TeachingLearning Process of Secondary Schools in Dhaka (Bangladesh Journal of Psychology, 2026)
The Multiple Intelligence Theory (MIT), which categorizes human intelligence in a multidimensional framework, is considered one of the most influential psychological theories in education. The purpose of this study was to explore the application of different intelligence categories in secondary classrooms in Dhaka, the capital of Bangladesh. Specifically, the study aimed to determine the extent to which different MI categories are employed in teaching-learning activities, and whether gender-based differences exist among teachers regarding the use of MI categories. Using a quantitative observational design, systematic classroom observations were conducted in 20 secondary-level classrooms across 10 schools in Dhaka city. An observation checklist structured into 30-second intervals was used to record time spent on activities within each of the eight MI domains. Statistical analysis of percentage-based data revealed a predominance of traditional teaching-learning activities, primarily addressing verbal-linguistic and visual-spatial intelligences, indicating poor integration of MI categories in the secondary classroom context. Furthermore, noteworthy gender differences were observed in the preference for MI-associated teaching-learning activities between male and female teachers. The study concludes by recommending targeted teacher training programs and curriculum reforms to promote the integration of MI-based approaches in secondary education. Additionally, the study suggests further research to better understand the local educational context and to guide reform initiatives. Bangladesh Journal of Psychology, Vol. 26(1), June 2026, pp. 1-18